Reka Bentuk Rumah Tradisional Negeri Sembilan Dipengaruhi oleh Adat dan Kedaerahan: The Design of the Negeri Sembilan Traditional House that is Influenced by Customs and Regional Factors - Noor Hayati Ismail; Shahrul Kamil Yunus; Mastor Surat (Wacana Seni Journal of Arts Discourse, 2016)
The unique design of Negeri Sembilan traditional houses represents the indigenous perpatih custom or matrilineal kinship system practiced by the society in Negeri Sembilan. In fact, the design of the roof with its long tapering ends raised slightly at both sides has become the unique architectural identity of Negeri Sembilan. Although customs and regional factors have influenced the designs of the traditional houses, nevertheless the originality of the concept and philosophy of the architectural design of the house are often said to match the design of customary house in Minangkabau, Indonesia. This research aims to identify and analyse some of the differences in the traditional house designs in West Sumatera, Indonesia and Negeri Sembilan, Malaysia. This study will look at the evolution of the Negeri Sembilan traditional house design that originated from Minangkabau. Location studies involve several villages of traditional houses in Padang, Bukit Tinggi, Kampar Kiri, in West Sumatra, Indonesia and Rembau, Kuala Pilah, Tampin in Negeri Sembilan, Malaysia.